Impact of Expanded Criteria Variables on Outcomes of Kidney Transplantation from Donors After Cardiac Death. Issue 1 (January 2015) - Nagaraja, Pramod; Roberts, Gareth W.; Stephens, Michael; Horvath, Szabolcs; Kaposztas, Zsolt; Chavez, Rafael; Asderakis, Argiris
Abstract : Introduction: To expand the donor pool, kidney transplants are being performed using donors who were previously considered unacceptable. We applied the United Network for Organ Sharing criteria to define expanded criteria donors (ECD) within the donation after cardiac death (DCD) and donation after brain stem death (DBD) cohorts. We compared outcomes of DCD and DBD transplants with and without (standard criteria donor [SCD]) the ECD criteria. Methods: This was a single-center retrospective study of all deceased donor transplants from 2004 to 2010 (n=359). Four groups were identified—DBD-SCD (n=154), DBD-ECD (n=93), DCD-SCD (n=78), and DCD-ECD (n=34). Kaplan-Meier analysis of graft and patient survival and multiple regression analysis of 1-year graft function were performed. Results: One-year and two-year uncensored graft survivals were similar between DCD-ECD and DCD-SCD cohorts (1 year, 90% and 93%; 2 years, 81% and 93% respectively; log-rank test P =0.2). Median estimated glomerular filtration rate (eGFR) was lower in DCD-ECD recipients at 12 months (41 vs. 53 mL/min, P =0.003) and 24 months (33 vs. 54 mL/min, P <0.001) compared with DCD-SCD recipients. Compared with DBD-ECD recipients also at 24 months, DCD-ECD recipients showed a lower graft function (median, eGFR 33 vs. 47 mL/min; P =0.007) but similar graft survival. Expanded criteria donor status (B=−9.7, P =0.01) was associated with a lower 1-year eGFR within the DCD cohort, with donor age (B=−0.42, P =0.002) being the only significant ECD variable. Conclusion: Short-term graft survival in DCD-ECD transplants was comparable to DCD-SCD and DBD-ECD transplants albeit with poorer allograft function at 2 years. Quality-of-life studies are needed to determine the true value of these transplants, particularly when performed to older recipients. Abstract : In this single-center study, comparison of extended criteria donors (ECD) who suffered brain death (DBD) versus cardiac death (DCD) demonstrated that ECD/DCD transplants resulted in lower renal function but similar short-term graft survival to ECD/DBD transplants.